2018
DOI: 10.1186/s12894-018-0328-5
|View full text |Cite
|
Sign up to set email alerts
|

Mannitol reduces nephron loss after warm renal ischemia in a porcine model

Abstract: BackgroundMannitol has been employed to ameliorate renal warm ischemia damage during partial nephrectomy, however, there is limited scientific evidence to support the use of mannitol during partial nephrectomy. The objective of the present study was to investigate the glomerular number after renal warm ischemia, with and without the use of mannitol in a Pig Model.MethodsTwenty-four male pigs were assigned into three groups. Eight animals were allocated to the sham group that was subjected to laparoscopic disse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 23 publications
0
12
0
1
Order By: Relevance
“…14,17 In a recent study, Damasceno-Ferreira et al demonstrated in a pig model that mannitol could prevent glomerular loss during warm ischaemia. 19 Clinical parameters, including urea and creatinine concentrations, did not change significantly. 19 Moreover, mannitol was proposed to act as an oxygen free radical scavenger attenuating ischaemia reperfusion injury.…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…14,17 In a recent study, Damasceno-Ferreira et al demonstrated in a pig model that mannitol could prevent glomerular loss during warm ischaemia. 19 Clinical parameters, including urea and creatinine concentrations, did not change significantly. 19 Moreover, mannitol was proposed to act as an oxygen free radical scavenger attenuating ischaemia reperfusion injury.…”
Section: Introductionmentioning
confidence: 90%
“…19 Clinical parameters, including urea and creatinine concentrations, did not change significantly. 19 Moreover, mannitol was proposed to act as an oxygen free radical scavenger attenuating ischaemia reperfusion injury. 20e22 Haraldsson et al and Khoury et al could observe an effect of mannitol on direct and indirect renal ischaemia reperfusion injury in animals.…”
Section: Introductionmentioning
confidence: 90%
“…Similar to the effects of urea, decreased renal tubular swelling has also been described when mannitol is given after reperfusion, although this observed feature is of unknown physiologic significance [28]. A differential impact of contralateral renal effects can also confound studies, whereas solitary kidney models may demonstrate a different pre-existing renal physiology and mannitol response in ischemia models [20,29]. Finally, it is notable that preclinical study results demonstrate only short-term physiologic shifts without a correlation to long-term functional benefits suggesting transient, artificial changes, as previously noted [30].…”
Section: Mannitol Mechanism Of Action and Ischemia Reperfusionmentioning
confidence: 99%
“…Mathematical models have estimated that a 50% decrease in GFR requires a four-fold reduction in glomeruli from baseline [37]. This was demonstrated in an animal model with mannitol, in which IRI led to a decrease of 1.14-0.89 million glomeruli without measurable change in GFR [29]. Solitary kidney models may offer some insight into renal compensatory change.…”
Section: Renal Function Preservation In Pnmentioning
confidence: 99%
“…Histological evaluation of kidneys demonstrates that mannitol significantly decreased tubular necrosis and inflammatory infiltration [81]. A recent study used the porcine model of I/R with positive results: kidneys subjected to ischemia displayed decreased weight, volume, and number of glomeruli in comparison to the sham operated and mannitol groups and concluded that using this antioxidant significantly reduces nephron loss during warm ischemia in this animal model [107].…”
Section: Antioxidants and Renal I/r Injurymentioning
confidence: 99%